Review: In vitro Cell Platform for Understanding Developmental Toxicity - Xie, Junkai; Wettschurack, Kyle; Yuan, Chongli (Frontiers in Genetics, 2020)
Developmental toxicity and its affiliation to long-term health, particularly neurodegenerative disease (ND) has attracted significant attentions in recent years. There is, however, a significant gap in current models to track longitudinal changes arising from developmental toxicity. The advent of induced pluripotent stem cell (iPSC) derived neuronal culture has allowed for more complex and functionally active in vitro neuronal models. Coupled with recent progress in the detection of ND biomarkers, we are equipped with promising new tools to understand neurotoxicity arising from developmental exposure. This review provides a brief overview of current progress in neuronal culture derived from iPSC and in ND markers.